IMPLEMENTASI ASESMEN KEBUTUHAN BERBASIS DATA DALAM PENYUSUNAN RENCANA PENGEMBANGAN SEKOLAH: STUDI KASUS DI SMAN 1 SAMPANAHAN - Hafizi, Rahmani; Suyoto, Suyoto; Rahmadi, Rahmadi; Sulistiyana, Sulistiyana (Jurnal Manajemen Pendidikan, 2025)
In the context of education, needs assessment serves as a basis for developing relevant and priority development plans. This study aims to describe and analyze the implementation of data-driven needs assessment in the development planning process of SMAN 1 Sampanahan. Effective educational planning should begin with an accurate assessment of needs to ensure that school policies and programs align with the actual conditions of the educational unit. This research employs a descriptive qualitative approach, utilizing in-depth interviews, participatory observations, and document analysis. The findings indicate that SMAN 1 Sampanahan has utilized various assessment tools such as internal surveys, academic performance data, and program evaluation results to identify priority needs. The assessment process involves school principals, teachers, and the school committee as key stakeholders. However, challenges remain in data integration and consistency of need reporting across departments. These findings highlight the importance of data literacy capacity to support needs-based planning at the school level. This study recommends strengthening digital-based assessment systems and providing data-driven decision-making training for educators and school personnel.